DEFINING GREEN ROAD PROJECT MANAGEMENT SCOPE BY PDRI - An-Pi Chang; Jyh-Dong Lin (International Journal of Engineering Technologies and Management Research, 2018)
This study is about the project early operation content of the green road development, takes full account of the operation items of various stages of the life cycle, by the use of special case define the Project Definition Rating Index (PDRI). PDRI assessment framework, defining the need and scope of green road project development operations in the metropolitan area, and inquire set various assessment indicators of the work to complete building the overall indicator assessment system. From research in a policy aspect, as well as data collection out of instances of project case, research program obtains evaluation index operation item, and by semistructured interviews supplements insufficient evaluation index items and particularity needs. Research results will be beneficial to the application in the metropolitan regional overall development project. Building green road index evaluation system helps to avoid the environmental impact brought about by land development, reduce damage to people's life safety as a consequence from needs for road maintenance, alleviate future maintenance and management expenses, and is in line with the expected benefit of green road project sustainable development.